A retrospective single-center study of transnasal ileus tube insertion accompanied with cap-assisted endoscopic advancement for malignant adhesive bowel obstruction - Su-Yu Chen; Rui Huang; Yu Zhang; Zhao-Fei Xie; He Huang; Hong Shi (Scientific Reports)
Abstract To investigate the effectiveness of cap-assisted endoscope synchronous advancement and tube direction adjustment for inserting transnasal ileus tubes in patients with malignant adhesive bowel obstruction (MABO). 25 patients with cap-assisted endoscopic synchronous method (Group A, Dec 2023–Apr 2024) were reviewed retrospectively. Accordingly, those with forceps-grasping method (Group B: 27, Aug 2022–Nov 2023) were included as controls. Both groups were similar in terms of age, sex, primary tumor, doctor experience distribution and technical success rate. The proportion of gynecological cancers was the highest in either group. The time required for insertion was shorter in Group A than in Group B (5 vs. 12 min; P = 0.000). Group A also had slightly longer tube insertion length than Group B (129.8 ± 14.1 vs. 121.3 ± 12.0 cm; P = 0.008), and the remission rate of intestinal obstruction symptoms in Group A was similar to that in Group B (75.0% vs. 74.1%; P = 0.940). There were no significant differences in complications between the two groups. One patient suffered MABO recurrence 14 days after withdrawal of the tube. Our findings indicate that transnasal ileus tube insertion with cap-assisted endoscopic synchronous method took shorter time and had the same rate of technical success and advantage of decompression compared with forceps-grasping method.